PEMANFAATAN TEKNOLOGI GADGET TERHADAP PENGARUH SOSIAL EMOSI AUD DALAM KONSEP PEMBELAJARAN LITERASI DIGITAL - Hilman Fauzi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
Today's challenges are very diverse, the rapid development of technology cannot be avoided by society. It is undeniable that technology is like an obligation to be possessed by every human being uncomplicated by early childhood at this time, the many uses of technology by early childhood become a problem today. Digital literacy is an effort in empowering the community so that people can follow the movement of the times including the early childhood education at this time, education today must be able to provide innovation because the age continues to develop continuously because practical education will continue to occur and is unique for each individual and society in different situations at different times. Early childhood was born in the age of technology, they are often fascinated by games and new technologies, this greatly affects patterns of human life both in terms of thought patterns and behavior. With digital literacy learning in the early childhood stage, it is hoped that this nation can achieve the expected progress.